MEROPENEM INDUCED HEPATIC DERANGEMENT: A CASE REPORT - Ullah, Asmat; Sabir Ali, Sobia (Journal of Postgraduate Medical Institute, 2020)
Drug-induced hepato-toxicity is one of the common causes of nosocomial morbidity leading to increased length of hospital stay as well as higher mortality. A variety of drugs may lead to different types of hepatobilary disorders. Meropenem, is a broad spectrum antibiotic generally prescribed for complicated infection and in intensive unit cases. It is rarely associated with elevation of hepatic enzymes. We report a case of 56-year-old man who was admitted for complicated diabetic foot and discharging abscess for the past one week. Meropenem was prescribed intravenously for septicemia. However, after 7 days of administration, there was gross elevation of alkaline phosphatase with normal alanine aminotransferase and bilirubin. His INR and hepatobilary sonograph was repeatedly normal. On discontinuation of Meropenem, there was normalization of alkaline phosphatase and resolution of his symptoms.